Sequência didática para o ensino da cinemática relativística por meio das TICs - Yamashita, Fábio Kazuyuki de Souza (2020)
Albert Einstein's Theory of Special Relativity (TRR) revolutionized the way we understood concepts for a long time considered absolute as space and time. With considerably counter intuitive definitions, TRR has become one of the pillars of Modern Contemporary Physics (FMC) and has provided a range of technologies that are present today in our daily lives. In view of the importance of this knowledge in the formation of critical citizens capable of understanding and associating information related to FMC, this work aims to propose a didactic sequence that, based on David Ausubel Theory of Meaningful Learning and the use of information and communication technologies (ICT), enables the teacher to debate and develop knowledge about relativistic kinematics with his high school students.